2009
DOI: 10.1007/s12020-009-9213-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of composite whole body insulin sensitivity index derived from mixed meal test and oral glucose tolerance test in insulin resistant obese subjects

Abstract: Apart from fasting blood glucose (FBG) and insulin (FBI), oral glucose tolerance test (OGTT) is also used in calculating insulin sensitivity. During OGTT, insulin secretion may not reflect normal physiological insulin secretion. Based on this idea, hepatic and whole body insulin sensitivity rates were tested during OGTT and mixed meal test (MMT) in obese subjects. Thirty-one women with Quantitative Insulin Sensitivity Check Index (QUICKI) values below 0.350 and body mass index (BMI) >or=30 were included into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…This difference was due to a significant 30 % reduction in the insulin response in males of Yemenite origin (p = 0.03), while women of Yemenite origin had similar early insulin response. In contrast, there was no difference in insulin sensitivity between the two groups indicated by similar Matsuda index that was found previously, to be highly correlated with the gold-standard euglycemic clamp [12,13] (Fig. 1c).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…This difference was due to a significant 30 % reduction in the insulin response in males of Yemenite origin (p = 0.03), while women of Yemenite origin had similar early insulin response. In contrast, there was no difference in insulin sensitivity between the two groups indicated by similar Matsuda index that was found previously, to be highly correlated with the gold-standard euglycemic clamp [12,13] (Fig. 1c).…”
Section: Resultssupporting
confidence: 80%
“…The usage of meal tolerance test as an alternative method to determine indices of insulin secretion and insulin sensitivity is supported by previous studies that have shown it to be highly correlated with the results provided by the oral glucose tolerance test (OGTT) with the advantage of being a more physiologic stimulus [13][14][15].…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Insulin resistance was estimated by two different surrogate measuresments: the homeostatic model assessment (HOMA-IR) index, calculated from fasting plasma insulin (FPI) and fasting plasma glucose (FPG) concentrations [FPI (mU/l) ϫ FPG (mmol/l)/22.5], and Matsuda's composite index, calculated using both fasting and postprandial concentrations of insulin and glucose [10,000/(FPI ϫ FPG ϫ mean insulin levels during MTT ϫ mean glucose levels during MTT)1/2]. Because the relationship between insulin and glucose concentrations during the fasting state reflects mainly the balance between hepatic glucose output and insulin secretion, it is generally accepted that the HOMA-IR is an indicator of hepatic insulin resistance (28,29,39,46). However, during the postabsorptive state, insulin sensitivity equally reflects both suppression of hepatic glucose production and glucose disposal by all tissues in the body, and therefore, Matsuda's composite index is generally considered an indicator of whole body insulin sensitivity (28,39).…”
Section: Methodsmentioning
confidence: 99%
“…Because the relationship between insulin and glucose concentrations during the fasting state reflects mainly the balance between hepatic glucose output and insulin secretion, it is generally accepted that the HOMA-IR is an indicator of hepatic insulin resistance (28,29,39,46). However, during the postabsorptive state, insulin sensitivity equally reflects both suppression of hepatic glucose production and glucose disposal by all tissues in the body, and therefore, Matsuda's composite index is generally considered an indicator of whole body insulin sensitivity (28,39). Accordingly, whole body insulin resistance is estimated by calculating the inverse number of Matsuda's composite index.…”
Section: Methodsmentioning
confidence: 99%